2017
DOI: 10.1038/s41598-017-04135-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight and obesity in 15.8 million men aged 15–49 years in rural China from 2010 to 2014

Abstract: Obesity has been increasing worldwide. Data on obesity status among men of reproductive age are scarce. This study aimed to assess the national prevalence and trend of overweight and obesity among reproductive-age men in rural China. In the nationwide population-based study, data were obtained from the National Free Preconception Health Examination Project in rural China from 2010 to 2014. Weight and height were measured in 16 161 982 men aged 15–49 years and their female partners (15 997 739 participants aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 24 publications
4
64
2
2
Order By: Relevance
“…However, the global obesity rate is still increasing as the trends have accelerated in other regions of the world, where most people live. The increase in the prevalence of obesity in developing countries is mainly due to rapid changes in socioeconomic status and demographic, and the adoption of an energy-and fat-rich diet and a sedentary lifestyle [17]. In 1980, the South East Asian, Western Pacific and African regions were those with the lowest prevalence of obesity, which was as low as 0.4% in Vietnam and b2% in nine other countries: Bangladesh (0.6%), China (0.6%), Ethiopia (1.2%), Indonesia (1.4%), Myanmar (1.5%), Nigeria (1.7%), India (1.7%), Japan (1.8%), and South Korea (1.9%).…”
Section: Discussionmentioning
confidence: 99%
“…However, the global obesity rate is still increasing as the trends have accelerated in other regions of the world, where most people live. The increase in the prevalence of obesity in developing countries is mainly due to rapid changes in socioeconomic status and demographic, and the adoption of an energy-and fat-rich diet and a sedentary lifestyle [17]. In 1980, the South East Asian, Western Pacific and African regions were those with the lowest prevalence of obesity, which was as low as 0.4% in Vietnam and b2% in nine other countries: Bangladesh (0.6%), China (0.6%), Ethiopia (1.2%), Indonesia (1.4%), Myanmar (1.5%), Nigeria (1.7%), India (1.7%), Japan (1.8%), and South Korea (1.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Globally, one in four men and one in five women, in total 1.13 billion adults, had high blood pressure in 2015 [4]. Similarly, overweight/obesity is becoming a globally epidemic issue [6,7]. As one of the most common risk factors for hypertension, excess weight gain can be the cause of 78% of primary hypertension in men and 65% in women [8].…”
Section: Introductionmentioning
confidence: 99%
“…This frequency is higher that China (33.8%) and lower that U.S. rates (65.5%) [14,15]. It can be observed that in BMI values are higher in older men (p<0.01).…”
Section: Resultsmentioning
confidence: 72%